Zn–Co-MOF on solution-free CuO nanowires for flexible hybrid energy storage devices. (March 2022) - Hussain, Iftikhar; Iqbal, Sarmad; Hussain, Tanveer; Cheung, Wai Lok; Khan, Shakeel Ahmad; Zhou, Jun; Ahmad, Muhammad; Khan, Shahid Ali; Lamiel, Charmaine; Imran, Muhammad; AlFantazi, Akram; Zhang, Kaili
Abstract: Pouch-type supercapacitor was developed by employing flexible Zn–Co-metal organic framework (MOF)@CuO and porous reduced graphene oxide as active electrodes. The flexible Zn–Co-MOF@CuO was fabricated by a facile two-step strategy. In the first step, Cu mesh was oxidized to cupric oxide (CuO) by a solution-free treatment. In the second step, Zn–Co-MOF was deposited on CuO scaffold through a solvothermal treatment. The as-prepared integrated Zn–Co-MOF@CuO exhibited excellent flexibility at different bending angles. The flexible Zn–Co-MOF@CuO displayed excellent electrochemical activity during three-electrode testing due to the merits of high electrical conductivity and an existence of p-n heterojunction between CuO and Zn–Co-MOF. The as-fabricated pouch supercapacitor yielded a high energy density of 41 W h kg −1 at a current density of 1 A g −1 and an excellent cycling stability of 97% after 20, 000 cycles. Structural and superior electronic properties of Zn–Co-MOF@CuO were further verified through first principles calculations based on density functional theory (DFT), which perfectly supported the experimental results. The excellent electrochemical attributes of the flexible pouch supercapacitor show immense promise for next-generation electrochemical energy storage devices. Graphical abstract: Image 1 Highlights: Flexible Zn–Co-MOF anchored on solution-free 1D CuO is prepared. The p-n heterojunction Zn–Co-ZIF@CuO exhibits higher capacity than bare CuO and bulk MOF. DFT was employed to study the enhanced electronic conductivity of Zn–Co-ZIF@CuO. The flexible SC gadget obtained a competitive energy density with improved cyclic stability.